Soins, lien social et responsabilité - Saillant, Francine; Gagnon, Éric (Anthropologica, 2022)
This paper suggests a reading of ideal conditions for care relation as interpreted by workers in the field of home care in three Quebec regions and covering three kinds of organisms (benevolent, private, and social economy organizations). Respect, time, confidence, security, and liberty are conditions which underlie the "good relation" that is sought by a worker arriving as a stranger in a customer residence. The relation is also a source of social bonding, a bond which tends to be a combination of the relationship models of the professional, the friend and the relative. The authors propose a reflection on the question of dependency in contemporary society, the ways in which it could be tackled, the relations that it supposes or requires, and the connections that the State tries to design or guide. Moreover, from the standpoint of the interveners, the building of the relationship tends to combine the universal (equality and equity with respect to care) with the singular (humanization, consideration for differences).